PENGARUH STRESS PSIKOLOGIS TERHADAP PASIEN PSORIASIS - Sinaga, Dameria (Jurnal Ilmiah Widya, 2013)
Psoriasis is one of dermatological conditions derived from dermatitis eritrosquamose disease which its etiology remains unclear, although stress, infection, trauma, endocrine disorder and alcohol. Psoriasis is a chronic residue condition, marked by appearance of eritematous patch with a straight border, mica like transparent and thick squander, wax, Auspitz and Kobner phenomenon. The purpose of the research is to determine the psychological stressor factors in psoriasis as well as relations with the nor stress hormone epinephrine. The methods used observational case control study. Psoriasis Diagnosis is made by clinical features, histopathological examination, interviews how to detect stress. The results show that psychological stress factors play role in psoriasis and there is a positive link between the severity of neither psoriasis koelasi with nor epinephrin. Psoriatic patients (1) may suffer psychologically due to their physical (skin) change, (2) develop an arthritic inflammation and nail deformities in the future.